CO2 absorption by piperazine promoted aqueous ammonia solution: absorption kinetics and ammonia loss. Issue 3 (30th May 2013) - Li, Lichun; Han, Wenfeng; Yu, Hai; Tang, Haodong
Abstract: Aqueous ammonia (NH3 ) solution has been proposed as a promising absorbent for post‐combustion capture of carbon dioxide (CO2 ). However, when aqueous NH3 is used alone, the capture process suffers from a low CO2 absorption rate and high NH3 loss. In this study, we measured CO2 mass transfer coefficients and NH3 loss rate in a wetted wall column study of CO2 absorption in piperazine (PZ) promoted aqueous NH3 solution, at NH3 concentrations of 0.59–4.12 mol/L (M), CO2 loadings (molar ratio of CO2 /NH3 ) of 0 to 0.5, temperatures of 283.15–298.15 K. The second‐order rate constants for the reactions of CO2 with PZ and NH3, which are determined based on the kinetic results from the wetted wall column, agree reasonably well with published values. Addition of PZ to aqueous NH3 can significantly increase mass transfer coefficients of CO2 in aqueous NH3, but at the expenses of an increase in NH3 loss. The enhancement by addition of PZ is due to the fast reaction of CO2 with PZ and PZ carbamate. However, addition of PZ to aqueous NH3 increases the concentration of free NH3 in the solvent, thereby increasing NH3 loss.